2004
DOI: 10.1002/jrs.1120
|View full text |Cite
|
Sign up to set email alerts
|

Lattice vibrations and thermal conductance of Li2O(B2O3)3 crystals

Abstract: Li 2 O·3B 2 O 3 or Li 2 O.B 2 O 3 / 3 (LOBO) crystallizes in the orthorhombic space group Pna2 1 with cell parameters a = 0.73788(6), b = 0.84473(7) and c = 0.51395(5) nm and two formula units in the primitive cell. Raman results show that the characteristic spectra of LOBO are mainly contributed by particularly the B(3) -O tetrahedra and also the B(1) -O and B(2) -O triangles and partly ascribed to the breathing vibrations of the B -O rings. The structural rigidity of LOBO is associated with all B -O bond str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The role of CeO 2 as a network former at the expense of its role as a network modifier increases simultaneously with increasing the molar ratio Li 2 O/B 2 O 3 . It can be concluded that most of CeO 2 content is associated with B 2 O 3 network to convert BO 3 into BO 4 − units. The role of cerium oxide as a TMO in the conductivity behaviour was suppressed by the role of Li + ion as a small and highly conductive ion.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The role of CeO 2 as a network former at the expense of its role as a network modifier increases simultaneously with increasing the molar ratio Li 2 O/B 2 O 3 . It can be concluded that most of CeO 2 content is associated with B 2 O 3 network to convert BO 3 into BO 4 − units. The role of cerium oxide as a TMO in the conductivity behaviour was suppressed by the role of Li + ion as a small and highly conductive ion.…”
Section: Resultsmentioning
confidence: 98%
“…IR spectroscopic study of CeO 2 -B 2 O 3 glasses [6] showed that at CeO 2 less than 40 mol%, cerium oxide plays the role of network former. For higher concentrations, CeO 2 would play a dual role; most of CeO 2 plays the role of network modifier to change BO 3 into BO 4 − units and some CeO 2 plays the role of network formers (O = bridging oxygen). In all cases, introducing CeO 2 into the B 2 O 3 network would increase the crosslinking of the glass matrix due to the increasing number of CeO 4 and/ or BO 4 − groups in the glass skeleton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in a primitive cell and Pna2 1 (C 2v 9 ) space group [27]. Since above space group does not contain an inversion center, the IR active modes are simultaneously Raman active and these modes are nondegenerate [28]. In the present study, we acquired Raman spectra of single crystals and observe 31 Raman active modes in the spectral range of 90-900 cm -1 at room temperature.…”
Section: Temperature Dependent Raman Spectroscopymentioning
confidence: 85%
“…The crystal Raman spectrum (Fig. 2(a)) possesses all the spectral characteristics of a LBO crystal, 15,16 indicating that the crystal is LBO. The melt Raman spectrum (Fig.…”
Section: Resultsmentioning
confidence: 99%